'I didn't have any option': experiences of people receiving in-centre haemodialysis during the COVID-19 pandemic. (2nd May 2022) - Danton, Ian; Kapadi, Romaana; Elander, James; Louth, Charlotte; Selby, Nicholas M; Taal, Maarten W; Stalker, Carol; Mitchell, Kathryn
Abstract : Background/Aims: People receiving in-centre haemodialysis (ICHD) during the COVID-19 pandemic had to adjust to more challenging treatment conditions. This article aims to explore people's experiences of adjustment to ICHD during the pandemic. Methods: Thematic analysis of in-depth, semi-structured interviews with 14 adult UK ICHD patients. Findings: A total of four themes were identified: perceptions of the threat, impacts on treatment, impaired communication and coping and positive adjustment. These themes described participants' experiences of vulnerability to COVID-19; the ways the pandemic affected dialysis and clinical care; the impact that measures to reduce viral transmission had on communication and interaction within dialysis units; and ways that participants coped and made positive adjustments to the adversities imposed by the pandemic. Conclusions: The findings give insights into adjustment during extreme adversity. They also help to identify how support for ICHD patients could be improved as pandemic conditions recede and ways that dialysis units could prepare for future outbreaks of infectious illness.